Lack of evidence of mastitis as a causal factor for postpartum dysgalactia syndrome in sows1, 2, 3. Issue 1 (11th October 2019) - Kaiser, Marianne; Jacobson, Magdalena; Bækbo, Poul; Dahl, Jan; Jacobsen, Stine; Guo, Yong Z; Larsen, Torben; Andersen, Pia H
Abstract: To investigate the prevalence of mastitis in sows suffering from postpartum dysgalactia syndrome (PDS ), we examined milk constituents and concentrations of lipopolysaccharides (LPS ) obtained from the udder vein (v. epigastrica). As part of a case–cohort study, 109 sows were monitored daily from 60 h antepartum (a.p. ) to 36 h postpartum (p.p. ). Over time, 38 sows were diagnosed with PDS (PDS+) and were retrospectively matched with 38 healthy sows (PDS−). The study period was divided into 7 smaller time periods (A, B, C, D, E, F, G, H, and E), allowing the studied values, in period B to G, to be compared with period A that served as a baseline, and PDS+ and PDS− sows were compared within the time periods. All sows were subjected to a thorough daily clinical examination and blood was sampled from v. epigastrica for LPS detection. Milk samples were obtained for bacteriological evaluation and detection of N -acetyl-beta-d-glucosaminidase (NAGase ), lactate dehydrogenase (LDH ), β-glucuronidase (β-glu ; for evaluation of mastitis), isocitrate (isoC ), free glucose, uric acid (UA ; for evaluation of the mammary energy status), β-hydroxybutyrate acid (BHBA ; for evaluation of ketosis), and milk urea (for evaluation of the protein status). The results revealed that PDS+ sows had decreased concentrations of UA in milk ( P < 0.0001), increased heart rates ( P < 0.01), increased mammary edema ( P < 0.05), and prolonged capillary refill time in the vulvar mucosa ( P < 0.01) compared with PDS− sows. Compared with baseline, feces became more solid 0 to 36 h p.p. ( P < 0.0001) and the respiration rate decreased 12 to 24 h p.p. ( P < 0.0001) for both PDS+ and PDS− sows. No differences were found between PDS+ and PDS− sows for severe bacterial infections, concentrations of LPS in blood or LDH, NAGase, BHBA, free glucose, isoC, or urea in milk. Concentrations of LPS in blood were not associated with signs of mastitis or edema in the mammary glands. However, a difference over time was seen for redness ( P < 0.0001), warmth ( P < 0.0001), and hardness ( P < 0.05) of the 6 most anterior glands in both PDS+ and PDS− sows from 60 h a.p to 36 h p.p. The PDS− sows had greater concentrations of β-glu than the PDS+ sows, but no change over time was demonstrated for this marker. In conclusion, signs of mastitis were not consistently linked to PDS in sows. However, the cardiovascular system seemed to be compromised in PDS+ sows and the cause should be investigated to elucidate the pathogenesis of PDS.